2019
DOI: 10.1097/inf.0000000000002384
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pregnant Women and Healthcare Professionals Toward Clinical Trials and Routine Implementation of Antenatal Vaccination Against Respiratory Syncytial Virus: A Multicenter Questionnaire Study

Abstract: Attitudes of pregnant women and healthcare professionals towards clinical trials and routine implementation of antenatal vaccination against respiratory syncytial virus: a multi-centre questionnaire study Wilcox,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 35 publications
6
55
1
Order By: Relevance
“…In our study, midwives would be less likely to support pregnant women becoming vaccinated against SARS-CoV-2 than obstetricians or GPs. These differences in attitudes across professions are consistent with the findings of previous studies on pregnancy or childhood vaccination [ 37 , 38 ]. The reasons are multiple, but a majority of the midwives are waiting for guidelines from their society or the ministry of health.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, midwives would be less likely to support pregnant women becoming vaccinated against SARS-CoV-2 than obstetricians or GPs. These differences in attitudes across professions are consistent with the findings of previous studies on pregnancy or childhood vaccination [ 37 , 38 ]. The reasons are multiple, but a majority of the midwives are waiting for guidelines from their society or the ministry of health.…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge was commonly measured by summary scores of correct answers to factual questions [ 41 , 71 , 97 , 101 , 107 , 109 , 111 , 113 , 119 , 126 ] or self-reported scales, which were more reflective of the provider’s perception of their knowledge [ 56 , 86 , 93 ]. One study found HCP self-rated knowledge of vaccine predicted their recommendation, but knowledge measured by factual questions did not [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…Providers knowledgeable about HPV were more likely to recommend the vaccine [ 41 , 50 , 101 , 123 ] (1.9–3 times) [ 41 , 101 ]. Likewise, providers with higher knowledge of RSV in pregnant women [ 86 ], pertussis in post-partum women [ 122 ], general influenza [ 91 ], maternal influenza [ 111 ], and 4CMenB [ 93 ] recommended the respective vaccines more frequently. Japanese providers aware of Guillain–Barre syndrome cases associated with U.S. influenza vaccination were less likely to recommend the vaccine during the 2009 H1N1 pandemic [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 There is evidence to suggest however that support amongst staff from may grow after implementation of such a service, once they observe that it indeed works in practice. 20,39 Institution-level barriers may include short appointments for antenatal visits, inadequate staffing and resources, lack of a suitable setting and facilities for safe vaccine storage and delivery, and concerns about appropriate insurance and financial reimbursement. 30,35,40 As well ensuring sufficient resources for the delivery of vaccination, it is important to note that resources and training must be in place to deal with any complications or side-effects that arise following vaccination.…”
Section: What Are the Barriers To Routine Implementation Of This Apprmentioning
confidence: 99%